Relationship among organizational commitment, job satisfaction, and job involvement among school teachers - Diskienė, Danuta; Tamoševičienė, Katažyna (Information & Media, 2015)
The importance of analysing organizational commitment is related to the managers’ need to know what kind of phenomena related to organizational commitment they should primarily pay attention to. Organizational commitment, job satisfaction, and job involvement are the three related phenomena which are important for satisfacting both the individual and organizational needs. This paper presents a theoretical model of relationship between organizational commitment and its dimensions (affective, normative, and continuous), job satisfaction, and job involvement which was structured on the base of different reasearch findings. Survey among schoolteachers was accomplished with reference to the presented model. Theresults of the study highlighted the existing relationship among organizational commitment, job satisfaction, and job involvement.